Analisis Eksistensi Kearifan Lokal Huyula Desa Bongoime Provinsi Gorontalo - Faris Budiman Annas; Ekawati Sri Wahyuni (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2014)
This study aims to analyze the existence of local wisdom Huyula measured by knowledge, attitudes and behavior of farmers to Huyula and its relationship with the internal and external factors farmers. The sample was Bongoime villagers who work as rice farmers. This study uses quantitative data with qualitative data furnished. This study tested using Spearman rank correlation test with significance level 0,05 level. Results of this study indicate that Huyula is a values contained in the mutual aid society. Farmers have the high knowledge, attitude and behavior towards Huyula although in practice only in the cleaning of irrigation channels. There is a relationship between knowledge, attitudes and behavior of farmers toward Huyula. There are two variabel like age and extention intensity that affects the existence Huyula.Keywords: economic behavior, fisher, fisheries industrialization